Drawbacks in SMEs' EIS Applications Framework for Development of EIS for SMEs in Sri Lanka - Malawige, I.R.; Nanayakkara, L.D.J.F. (My University, 2016)
The Small and Medium Scale Enterprises/Industries (SMEs) function as a lifeline in the informal sector in Sri Lanka due to their significant contribution to the overall economy in terms of employment, exports, innovation, tax income, equitable income distribution, social stability, domestic resources usage, and regional development. However, in Sri Lanka, a majority of Enterprise Information System (EIS) applications have not been focused by those ‘small players’ in the economy. The paper first identifies factors that contribute to SMEs relatively lower level of attraction towards EISs, using TOE Framework, which was tested mainly to assess the organization willingness on ICT in developing countries. Finally, the paper explains the ways and means by which the EIS vendors, SME and IT policy makers can address the gap between the current level and the potential for SME EIS adoption. Therefore the research findings help SMEs to create business opportunities with EIS applications and combat pressures from competition. Further specific SME ICT needs to be addressed strategically, in order to ensure their competitive position in the economy, will be discussed
Keywords: SME; Enterprise Information Systems/EIS; Enterprise Resource Planning/ERP; TOE Framework; ICT Adoption.